Erythropoiesis-Stimulating Agents in the Management of Anemia in Chronic Kidney Disease or Cancer: A Historical Perspective - Aapro, Matti; Gascón, Pere; Patel, Kashyap; Rodgers, George M.; Fung, Selwyn; Arantes, Luiz H.; Wish, Jay (Frontiers in Pharmacology, 2019)
Abstract Anemia is common in patients with cancer or with chronic kidney disease (CKD). Although the introduction of erythropoiesis-stimulating agents (ESAs) has transformed the management of anemia, their use has been complicated by a number of factors including frequent guideline updates, safety concerns and, in the US, a Risk Evaluation and Mitigation Strategy (REMS) program, which aimed to ensure that the benefits of ESAs outweigh the risks. Many previous concerns around ESA use in cancer and CKD have been addressed by the reassuring results of post-approval studies, and biosimilar ESAs have been used in Europe for many years, with safety and efficacy profiles similar to originator products. This review describes the evolution of the use of ESAs from approval to the present day, discussing results from clinical studies of ESAs in cancer and CKD, and the influence of these findings on product labeling and guideline updates. We also discuss the impact of the introduction of ESA biosimilars in Europe, bringing cost savings and increased access to patients.